Post-earthquake Distress and Development of Emotional Expertise in Young Adults - Pistoia, Francesca; Conson, Massimiliano; Carolei, Antonio; Dema, Maria G.; Splendiani, Alessandra; Curcio, Giuseppe; Sacco, Simona (Frontiers in Behavioral Neuroscience, 2018)
After a natural disaster like an earthquake about 15% of the population experience a post-traumatic stress disorder (PTSD). However, even those without a diagnosis of PTSD can suffer from disorders of the affective sphere, including anxiety, depression and alteration of emotion recognition. The objective of this study was to investigate the neuropsychological and emotional profile of students living in the earthquake-affected areas of L’Aquila, Italy. A group of students living in L’Aquila at the time of the 2009 earthquake was recruited, and compared to a control group of students not living in any earthquake-affected areas. Participants were assessed by means of the Beck Depression Inventory scale, the State-Trait Anxiety Inventory, the Insomnia Severity Index, the Intolerance of Uncertainty Scale Short Form, the Uncertainty Response Scale, the Anxiety Sensitivity Index 3, and the Eysenck Personality Questionnaire-Revised Short Form. Participants also took part in two behavioral experiments aimed at evaluating their ability to recognize facial expressions (by means of the Ekman and Friesen Pictures of Facial Affect) and to evaluate emotionally evocative scenes (by means of the International Affective Picture System). Results showed that students living in the earthquake-affected areas had a general increase of anxiety and anticipation of threats. Moreover, students living in the earthquake-affected areas showed a significantly higher overall accuracy in recognizing facial expressions as compared to controls. No significant differences between the two groups were detected in the evaluation of emotionally evocative scenes. The novel result lies in the greater accuracy of earthquake victims in recognizing facial expressions, despite the lack of differences from controls in evaluating affective evocative scenes. The trauma exposure may have increased vigilance for threats in earthquake victims, leading them to systematically pay attention to potential signs of approaching threats, such as emotional facial expressions, thus progressively developing particular “emotional expertise”.